2015
DOI: 10.1039/c5ra11203f
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodeoxygenation of phenol as a bio-oil model compound over intimate contact noble metal–Ni2P/SiO2 catalysts

Abstract: 1% Pd–10% Ni2P/SiO2, from a Ni2P reducing noble metal precursor, presents a high activity and cyclohexanol or cyclohexane selectivity due to more active sites and electrons transferring from Ni2P to the noble metal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 25 publications
1
14
1
Order By: Relevance
“…For the 3.1 % NiO x ‐6.9 % Ni 2 P/SiO 2 catalysts, the conversion of phenol was 97.3 % and the selectivity of cyclohexane was 73.7 %. The yield of cyclohexane (71.7 %) over 3.1 % NiO x ‐6.9 % Ni 2 P/SiO 2 was much higher than that of the other three catalysts and those reported previously, which confirmed that there are distinct synergistic effects of oxygen vacancies in NiO x for hydrogenation and Lewis acid sites in Ni 2 P for deoxygenation (Figure ).…”
Section: Resultssupporting
confidence: 78%
“…For the 3.1 % NiO x ‐6.9 % Ni 2 P/SiO 2 catalysts, the conversion of phenol was 97.3 % and the selectivity of cyclohexane was 73.7 %. The yield of cyclohexane (71.7 %) over 3.1 % NiO x ‐6.9 % Ni 2 P/SiO 2 was much higher than that of the other three catalysts and those reported previously, which confirmed that there are distinct synergistic effects of oxygen vacancies in NiO x for hydrogenation and Lewis acid sites in Ni 2 P for deoxygenation (Figure ).…”
Section: Resultssupporting
confidence: 78%
“…It is well known that P sites in the phosphides have “ligand” (or electronic) and “ensemble” (or geometrical) effects on metal sites, and the metal phosphides have both metallic and acidic properties. Hence, several researchers have been applied them for the hydrodeoxygenation of biofuel model compounds, such as phenol, 4‐methylphenol, guaiacol, anisole, palmitic acid, methyl palmitate, methyl oleate, and so on. However, to the best of our knowledge, the bulk metal phosphide catalysts have not been reported in liquid phase HDO of FAL to 2‐MF …”
Section: Introductionmentioning
confidence: 99%
“…35 In the previous study, we systematically studied phenol HDO over Ni 2 P and Ni 2 P@Pd supported catalysts using autoclave reactors. 36,37 However, the main products are cyclohexane and cyclohexanol over these catalysts. Herein, the inuence of the HDO reaction conditions on the reaction products is investigated over the base metal phosphide in a xed bed.…”
Section: -34mentioning
confidence: 99%
“…36. In a typical preparation, 2.62 g Ni (NO 3 ) 2 $6H 2 O and 60 g urea were dissolved in 225 mL deionized water and stirred for 30 min.…”
Section: Catalyst Synthesismentioning
confidence: 99%